STUDY ON FRESHWATER FISH CULTIVATION IN TELAGA JAYA, GORONTALO DISTRICT: STUDI TENTANG BUDIDAYA IKAN AIR TAWAR DI TELAGA JAYA KABUPATEN GORONTALO - Frezy Paputungan (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Aquaculture is defined as an activity to produce aquatic biota (organisms) in a controlled manner in order to gain profit. Another definition of aquaculture is human intervention (efforts) to increase aquatic productivity. Fish are members of poikilothermic (cold-blooded) vertebrates that live in water and breathe with gills. Fish are the most diverse group of vertebrates with more than 27,000 species worldwide. The research method used is descriptive qualitative, namely by explaining and answering in more detail how freshwater fish are cultivated, the benefits and types of freshwater fish that are popularly consumed by the public. The results of the research show that there are several types of freshwater fish that are popularly consumed in Telaga Jaya, Gorontalo Regency, including tilapia fish, gourami, catfish, goldfish, tilapia, nilem fish and snakehead fish.